Does research and development expenditure cointegrate with the gross national income of ASEAN countries? - Fennee, Chong; Liew, Venus Khim-Sen; Rosita, Suhaimi (Serials Publications, 2016)
In order to successfully transform into a knowledge economy and eradicate poverty, many ASEAN countries have allocated a considerable amount of their yearly expenditures in research and development over the last decade. The objective of this paper is to examine the long-run relationship between research and development expenditure and gross national income of five major ASEAN countries - Thailand, Malaysia, Singapore, Indonesia and Philippines. The results of a cross-country panel data analysis performed in this study suggest that there is a long-run cointegration relationship between these two variables. Findings imply that higher research and development expenditure has a favorable impact on the long-run prosperity of these countries.